2010
DOI: 10.1007/s10750-010-0372-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental drivers for Coquillettidia mosquito habitat selection: a method to highlight key field factors

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(39 reference statements)
0
12
0
3
Order By: Relevance
“…Studies of the criteria involved in mosquito habitat selection have been carried out mainly on species of public health concern, such as Anopheles sp., Aedes sp., Culex sp., Toxorhynchites sp., and Wyeomyia sp. and show that site selection is strongly species dependent (Sérandour et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies of the criteria involved in mosquito habitat selection have been carried out mainly on species of public health concern, such as Anopheles sp., Aedes sp., Culex sp., Toxorhynchites sp., and Wyeomyia sp. and show that site selection is strongly species dependent (Sérandour et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…mosquitoes showed that the most suitable habitats were ponds with the presence of larval host plants such as Typha sp., Phragmites sp., and Juncus sp. (Sérandour et al 2010). The presence of larvae was significantly correlated with physical‐chemical factors and the optimal water characteristics were natural pH, low salt concentration, and a relatively low level of suspended particulate matter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations